Upaya Promotif Kesehatan Remaja Dengan Menjadi Generasi BTS (Baik Terencana Selalu) Di SMA Pusponegoro - Meyliya Qudriani; Seventina Nurul Hidayah; Ilma Ratih Zukrufiana (Jurnal Informasi Pengabdian Masyarakat, 2024)
Adolescence is a stage of human growth and development that occurs after childhood and before adulthood. Adolescents are a group that is always assumed to be in good health even though many teenagers die prematurely which can result from attempted suicide, violence, pregnancy that has complications that can actually be prevented or treated. In Adolescent Reproductive Health, Adolescents will face various complex problems related to physical changes, nutritional adequacy, psychosocial development, emotions and intelligence which ultimately lead to conflicts within themselves which then affect their health. The purpose of this community service activity is to increase knowledge about proper adolescent health, increase knowledge about early marriage, pre-marital sex and drugs, increase knowledge about BTS youth (Good Planned Always) and prepare as a generation that can continue higher education, work and work. , save and equip themselves with life skills. The implementation of this Community Service activity was carried out at Pusponegoro Vocational School with the target of class XII teenagers. The method used in the implementation of this activity is counseling which begins with measuring the knowledge of participants by filling out a questionnaire about knowledge of adolescent reproductive health and its problems. This community service activity was carried out based on the results of the analysis through interviews and observations with partners, namely Pusponegoro Vocational School. Based on the analysis, it was identified that there were several problems faced by partners, one of which was the lack of understanding of adolescent reproductive health. This service activity is a solution to increase adolescent knowledge, especially class XII students of SMK Pusponegoro regarding reproductive health and its problems.